Assembly of the Hydroxycinnoline Core via Hydrazide-Assisted Rh(III)-Catalyzed C–H Functionalization and Annulation - Kim, Suho; Park, Heon Kyu; Kang, Ju Young; Mishra, Neeraj Kumar; Kim, In Su (Synthesis, 2022)
The structural modification of phthalazinones and indazolones has emerged as a pivotal topic in catalytic C–H functionalization events. Herein we report the hydrazide-assisted rhodium(III)-catalyzed cross-coupling reactions of N-arylphthalazinones and N-arylindazolones with vinylene carbonate. This method provides direct access to tetracyclic hydroxycinnolines. Complete site-selectivity and functional group compatibility were observed.
Keywords: C–H functionalization; cinnolines; indazolones; phthalazinones; rhodium; vinylene carbonate